Landscapes of Investigation : Contributions to Critical Mathematics Education - Miriam Godoy Penteado; Ole Skovsmose (Open Book Publishers, 2022)
Creating landscapes of investigation is a primary concern of critical mathematics education. It enables us to organise educational processes so that students and teachers are able to get involved in explorations guided by dialogical interactions. It attempts to address explicit or implicit forms of social injustice by means of mathematics, and also to promote a critical conception of mathematics, challenging the assumption that the subject represents objectivity and neutrality. Landscapes of Investigation provides many illustrations of how this can be done in primary, secondary, and university education. It also illustrates how exploring landscapes of investigation can contribute to mathematics teacher education programmes. This edited volume is the result of a collaboration established through the Colloquium in Research in Critical Mathematics Education, which took place in 2016, 2018, and 2019 in Brazil. Its twenty-eight contributors are young researchers from Brazil, Chile, Colombia, India, Mexico and the USA, who are dedicated to the further development of critical mathematics education. Organised in eighteen chapters, the volume presents examples of engaging students from a diversity of social and economic backgrounds, age ranges, and abilities across different countries. The chapters present original findings on the social aspects of all levels of mathematics education. Landscapes of Investigation is of particular relevance to those with an interest in the potential of mathematics education to challenge social injustices.